DIABETES RISK IN ELDERLY RESIDENTS IN A VULNERABLE AREA OF NORTH LIMA - Remuzgo Artezano, Anika (2020)
Objective: To determine the risk of diabetes in the elderly who reside in a vulnerable area of North Lima. Material and Methods: A quantitative, descriptive and cross-sectional study was carried out. The population consisted of 82 older adults who attend the San Martín de Porres health facility - Peru. The technique used was the survey and the data collection instrument was the Findrisc that measures the risk of type 2 diabetes, which is composed of 8 questions. Results: In relation to the risk of diabetes in the elderly, the moderate level predominated with 47.6% (n = 39), followed by the slightly elevated level with 28% (n = 23), high risk with 12.2% (n = 10), low risk with 9.8% (n = 8) and very high risk with 2.4% (n = 2). Regarding its dimensions, age predominated, age older than 64 years old with 69.5% (n = 57), BMI predominated 25-30 with 52.4% (n = 43), abdominal girth predominated in Male 94-102cm or woman 80-88cm with 41.5% (n = 34), predominant hyperglycemia not present with 74.4% (n = 61), arterial hypertension predominant but present with 70.7% (n = 58), consumption of fruits and vegetables predominate but not every day with 69.5% (n = 57), exercise predominates but does not perform with 54.9% (n = 45), and family history predominates but does not present with 69.5 % (n = 57). Conclusions: Regarding the risk of diabetes, the moderate level predominated. In the FINDRISC indicators, the consumption of fruits and vegetables, and the performance of physical activity are more vulnerable.